2004
DOI: 10.1016/j.febslet.2004.10.064
|View full text |Cite
|
Sign up to set email alerts
|

Echinacea alkylamides modulate TNF‐α gene expression via cannabinoid receptor CB2 and multiple signal transduction pathways

Abstract: Echinacea plant preparations are widely used in the prevention and treatment of common cold. However, so far no molecular mechanism of action has been proposed. We analyzed the standardized tincture Echinaforce TM and found that it induced de novo synthesis of tumor necrosis factor a (TNF-a) mRNA in primary human monocytes/macrophages, but not TNF-a protein. Moreover, LPS-stimulated TNF-a protein was potently inhibited in the early phase but prolonged in the late phase. A study of the main constituents of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
159
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(173 citation statements)
references
References 32 publications
12
159
0
2
Order By: Relevance
“…Consequently, it is not surprising that the effects of the different Echinacea species on IL-1β and TNF-α were similar. Our findings that Echinacea tinctures augmented production of these cytokines are consistent with reports from both human (Barak et al 2002;Gertsch et al 2004;Randolph et al 2003) and rodent (Bodinet et al 2002;Luettig et al 1989;Rininger et al 2000;Stimpel et al 1984) model systems; however, two teams found no effect of Echinacea extracts on these cytokines (Elsasser-Beile et al 1996;Schwarz et al 2002). These differences may be due to species selection, plant organ selection, extraction method, or other experimental choices as discussed above.…”
Section: Consideration Of Original Datasupporting
confidence: 92%
“…Consequently, it is not surprising that the effects of the different Echinacea species on IL-1β and TNF-α were similar. Our findings that Echinacea tinctures augmented production of these cytokines are consistent with reports from both human (Barak et al 2002;Gertsch et al 2004;Randolph et al 2003) and rodent (Bodinet et al 2002;Luettig et al 1989;Rininger et al 2000;Stimpel et al 1984) model systems; however, two teams found no effect of Echinacea extracts on these cytokines (Elsasser-Beile et al 1996;Schwarz et al 2002). These differences may be due to species selection, plant organ selection, extraction method, or other experimental choices as discussed above.…”
Section: Consideration Of Original Datasupporting
confidence: 92%
“…The acetylenic fatty acyl groups vary in length from C 9 to C 18 . Extracts of the purple coneflower (Echinacea purpurea) have insecticidal, immunesystem-stimulating, and anti-inflammatory properties that are attributed to the acylamides [192]. Alkamides have been shown to affect root growth and morphology in Arabidopsis indicating a potential role in development [193].…”
Section: 34mentioning
confidence: 99%
“…For cytokine measurements, the plates were centrifuged, and an appropriate amount (usually 50 ml) of the supernatant serum was removed for immediate analysis. Isolation of PBMCs and T lymphocytes from peripheral whole blood was performed, as previously reported (39). Cell cultures.…”
Section: Plant Materialsmentioning
confidence: 99%